The role of project activity in the formation of future specialists - Seisenbayeva, Zhanar; Nuriev, Marat; Rauandina, Aitzhamal; Osmanova, Zeinep; ., RuslanSeitkaziyev (Opción, 2018)
Modern economic, technical and other activity make high requirements for the specialists, graduated from the higher education institutions. The rapid growth of information volumes, expansion of scales of human activity cause the necessity for reforming of society and education. Creation of the innovative economy, based on commercialization of the new scientific and technical ideas, requires essential change in the system of training of personnel. There is given the answer to questions:What are the project methods of training?What are the conditions on development of reflexive abilities?